2010
DOI: 10.1002/fam.1053
|View full text |Cite
|
Sign up to set email alerts
|

Absorptivity and its dependence on heat source temperature and degree of thermal breakdown

Abstract: SUMMARYThe spectral absorptivity of 62 products has been measured in the wavelength region of 0.3-20 m. Effective absorptivity for fire-induced heat radiation typically lies in the range of 0.75-0.95. It was found that the effective absorptivity varies significantly with the temperature of the heat source. This has implications on the heating of a surface. The effect is more important when the absorptivity is used as input for calculations of ignition temperature and thermal inertia. It was also found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 4 publications
4
32
0
Order By: Relevance
“…Försth and Roos [10], in their recent study, confirmed this global trend for wood and plastic samples (sometimes with a decrease between 4 μm and 6 μm). Their numerical results of the effective absorptance over the emitting ranges of different heater temperatures corroborate the global observation explained above concerning the difference of absorption between radiation emitted at wavelengths below and above 2 μm.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Försth and Roos [10], in their recent study, confirmed this global trend for wood and plastic samples (sometimes with a decrease between 4 μm and 6 μm). Their numerical results of the effective absorptance over the emitting ranges of different heater temperatures corroborate the global observation explained above concerning the difference of absorption between radiation emitted at wavelengths below and above 2 μm.…”
Section: Discussionmentioning
confidence: 60%
“…A non-exhaustive literature review [6][7][8][9][10][11] shows that the influence of the radiative characteristics of the heater source on the results is an area of concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmittance measurements are performed in a similar manner to the reflectance measurements described above, but with the sample positioned across the beam entry port in Figure 3. For more details the reader is referred to reference [17].…”
Section: Infrared Propertiesmentioning
confidence: 99%
“…(1) can be neglected. For an irradiation level of 50 kW m -2 the temperature of the helical coil in the cone calorimeter is ≈ 750 °C [17]. Inserting this temperature and using the reflectance spectrum in Figure 7, Eqs.…”
Section: Infrared Propertiesmentioning
confidence: 99%